2016
DOI: 10.1007/s12274-015-0968-7
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics-generated graphene oxide microspheres and their application to removal of perfluorooctane sulfonate from polluted water

Abstract: Monodisperse graphene oxide (GO) microspheres were synthesized via microfluidics technology as a novel adsorbent for rapid (in 2 min) and high efficiency (98%) removal of perfluorooctane sulfonate (PFOS) from water. This novel material is a potential solution for treatment of bioaccumulative organic polluted water. To achieve improved performance, Mg 2+ was introduced into GO, and the metal composite exhibited significantly improved PFOS removal efficiency owing to bridging and interaction between Mg 2+ and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Consequently, FeG and RemB could also potentially be laid down in landfill sites as a barrierlining in multi-liner systems to mitigate the leakage or migration of landfill leachates into the water table. Previous research has demonstrated the applicability of GO for PFOS-sorption (Zhao et al 2016). In this study, we prove that the performance of GO can be improved through strategic mineral-functionalisation, which makes FeG a better adsorbent (for a variety of PFASs, as shown in the section Remediation of a contaminated-site water sample).…”
Section: Batch Sorption Studiessupporting
confidence: 64%
See 2 more Smart Citations
“…Consequently, FeG and RemB could also potentially be laid down in landfill sites as a barrierlining in multi-liner systems to mitigate the leakage or migration of landfill leachates into the water table. Previous research has demonstrated the applicability of GO for PFOS-sorption (Zhao et al 2016). In this study, we prove that the performance of GO can be improved through strategic mineral-functionalisation, which makes FeG a better adsorbent (for a variety of PFASs, as shown in the section Remediation of a contaminated-site water sample).…”
Section: Batch Sorption Studiessupporting
confidence: 64%
“…However, there is a lack of studies that investigate the use of GBMs for PFAS-sorption. One study has reported the use of graphene oxide (GO), the most common graphene-derivative, for sorption of perfluorooctanesulfonate (PFOS) in the presence of magnesium ions (Mg 2þ ), owing to the ability of Mg 2þ to form a bridge between PFOS and GO (Zhao et al 2016). Similar demonstrations for PFOA and other PFASs are not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure B shows an XPS survey of the Pd‐SiO 2 /PFOS layer. As shown in Figure B‐1, C 1s core level can be deconveloted to 4 peaks, C‐C (284.78 eV), C‐O (287.18 eV), CF 2 (293.98 eV), and CF 3 (291.48 eV), where the last 2 peaks show the bonding of carbon with fluorine ions in PFOS. Si 2p core level is shown in Figure B‐2, where a strong peak related to SiO 2 is observed.…”
Section: Resultsmentioning
confidence: 95%
“…Zhao et al presented microfluidics‐generated GO microspheres and their application to removal of perfluorooctane sulfonate from polluted water. This novel material was a potential solution for treatment of bioaccumulative organic polluted water . Bao et al immobilized trypsin in the layer‐by‐layer coating of GO and chitosan on a piece of glass fiber to fabricate microchip bioreactor for efficient proteolysis; Fig.…”
Section: Application Of Graphene‐based Microfluidicsmentioning
confidence: 99%